Candida albicans colonization level in heat-cured acrylic and in vitro Valplast system - Silvia Alexandra Reinoso Ortíz; Cristian Roberto Sigcho Romero; Sandra Marcela Quisiguiña Guevara; Evelyn Gabriela Tirado Villacís (Universidad de Ciencias Médicas de La Habana, 2023)
Introduction: A large number of microorganisms invade the oral cavity and others live there. Those with greater pathogenicity, such as the fungus Candida albicans, are usually associated with sub-prosthesis stomatitis. Objective: To evaluate the level of Candida colonization in heat- cured acrylic and Valplast system used as dental prosthesis bases. Material and Methods: An observational, quasi-experimental study was carried out on a sample of 15 heat-cured acrylic plates and 15 Valplast system plates, subjected to contact with Candida albicans, which was activated in sabouraud agar, in a sterile environment and with the temperature conditions of oral cavity at 37 °C, for 48 hours. Results: There is an important difference between the polished valplast surfaces, observing a lower amount of CFU/ml compared to thermo-cured acrylic. The unpolished heat-cured acrylic surfaces outperformed the Valplast system with values greater than 100,000 CFU/ml. The level of colonization by this microorganism in thermo- cured acrylic and Valplast system denoted the existence of differences between the CFU/ml values and the groups of materials with polished and unpolished surfaces of thermo-cured acrylic and Valplast system, being less for this latest material. Conclusions: The colonization levels of Cándida albicans are lower for the Valplast system, compared to the thermo-cured acrylic ones, so the latter material has a greater capacity for the formation of biofilms of this fungus and a greater risk of producing Candidiasis on both polished or unpolished surfaces.